Pengaruh Kredit Usaha Tani (KUT) terhadap Peningkatan Produksi dan Pendapatan Usaha Tani Padi Petani - Rahmawati, Mariana Fitria; Mita, Adyla; Afdah, Umi; Umanailo, Muhamad Chairul Basrun; Zarliani, Wa Ode Al (Universitas Medan Area, 2024)
The purposes of this research are: a) to know the influence of Farm Operation Credit (KUT) toward the use of production and production facilities in rice farming, b) to understand the difference in production and income between the KUT farmers and non-KUT farmers, c) to know the problems in KUT return. The Data Analysis Method to find out the influence of farm Operation Credit toward the use of production facilities and the production in rice farming using product function analysis was estimated with Cobb Douglas Model; to differ the production function for rice farming toward KUT farmers and non-KUT farmers, Dummy Variable was used; while to know the productivities and income differences between KUT farmers and non-KUT farmers, cost and income analysis were used. Furthermore to find out the productivities and income on the average t-test was used. The result of the research showed ; a) the use of KUT have very significant influence toward the use of production facilities in rice farming; b) the productivities and income of KUT farmers were higher than those of non-KUT farmers; c) the KUT TP. 1998/1999 return in a research area was still a problem: Rp. 9,7 millions had not been returned (48% from total return of Rp. 20 millions)